“Eu não falo assim, mas eles fala”: uma análise geossociolinguística da concordância verbal de terceira pessoa do plural na mesorregião norte maranhense - SANTOS, Israel Ferreira (2021)
The variation in verb agreement has been identified as one of the identitarian traits of the Brazilian Portuguese (known as BP) for a diversified group of factors which lead to it. Based on that, this variation has been studied by a huge number of scholars, such as Lemle and Naro (1977); Scherre and Naro (1993, 2007); Monguilhott (2001, 2009); Monguilhott and Coelho (2002); Cardoso (2005); Oliveira (2005); Monte (2007); Faria (2008); Welchen (2009); Carvalho (2018), and so on. For this reason, this research aims to investigate the variation in verb agreement for third person plural (known as CV3PP) in Maranhão’s North mesoregion, especially in the cities of São Luís, Raposa and Pinheiro based on the collected data by the Atlas Linguístico do Maranhão project (ALiMA). This work is supported by the principles of the Dialectology Geolinguistic - Coseriu (1982); Chambers and Trudgill (1994); Ferreira and Cardoso (1994); Cardoso (2010); Elizaicin (2010); Thun (2017) - as well as the Variationist Sociolinguistic - Weinreich, Labov and Herzog (2006); Tarallo (2007); Labov (2008); Mollica (2015). In addition, as a consequence of the absence of one specific question on the ALiMA questionnaire which attends completely to this study topic, it has been considered all the constitutive parts of the ALiMA questionnaire to the construction of the corpus of the presented research. Then, after revising the transcriptions of the ALiMA data and applying some new transcriptions to São Luís, Raposa and Pinheiro’s inquiries, this study analyzed 16 inquiries: 8 from São Luís, and 4 from each one of the other cities mentioned. These cities’ informants’ profile are divided in: place of birth - one of three cities on the corpus; age group - I (from 18 to 30 years old), or II (from 50 to 65 years old); gender - male or female; level of education - any uncompleted elementary school or any college graduation in São Luís. In total there were produced 1171 oral speech data and they have been submitted to quantitative analysis at the Goldvarb X computer program (Sankoff, Tagliamont and Smith, 2005; Guy and Zilles, 2007), which resulted in linguistic maps aiming to visualize better the distributions of linguistic and extralinguistic variations into the observed cities in Maranhão. In order to analyse the phenomenon, it has been considered under this research both linguistic and extralinguistic variations, subject position, semantic feature of the subject, verb types, phonic salience of the verb, and formal parallelism as linguistic ones, and gender, age, level of education and place of birth as the extralinguistic. As a result of an analysis excluding the level of education factor, Goldvarb X pointed out that the linguistic group of factors seems to be relevant to the CV3PP occurrence, except that the verb type group of factors was not considered under this analysis. On the other hand, in an analysis covering the extralinguistic factors, the computer program affirmed that only the place of birth and gender factors can influence this verb agreement variation. For its two levels of education informants’ factors, the studies about São Luís only resulted in the schooling extralinguistic factor displaying as the most relevant factor to the CV3PP occurrence. When it comes to linguistic factors in São Luís, the dominant ones were the semantic feature of the subject followed by the phonic salience of the verb. Although among these main results, the influence of the gender and verb types factors attested distinct data from the previous ones about the CV3PP in the Brazilian Portuguese.